Effectiveness Of Local Traditional Medicine In Treating Mild Health Complaints - Fajar Susanti; Rezqiqah Aulia Rahmat; Sapnita Sapnita (International Journal of Health Sciences, 2026)
ABSTRACT Local traditional medicines have long been used by the community as an alternative treatment to overcome various minor health complaints. This study aims to analyze the effectiveness of the use of local traditional medicines in treating minor health complaints such as coughs, fever, and digestive disorders. The research method used a quantitative approach with a cross-sectional design on 120 respondents. Data were collected through questionnaires and analyzed using the chi-square test. The results showed that 70% of respondents who used traditional medicines experienced improvement in symptoms within 2–3 days. There was a significant relationship between the use of traditional medicines and improved health conditions (p<0.05). It was concluded that local traditional medicines are quite effective in treating minor health complaints. Keywords: Traditional Medicine, Minor Health, Herbal, Effectiveness